DESIGN AND FEATURES ANALYSIS OF GENERALIZED ELECTRONIC CONTENT-COMMERCE SYSTEMS ARCHITECTURE - Vysotska, Victoria; Chyrun, Lyubomyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
This article is dedicated to the development of standardized methods and software for information resources processing in electronic content commerce systems (ECCS). In this paper an actual scientific problem of methods and tools development and research of information resources processing in ECCS was solved with the use of designed classification, mathematical tools, software and generalized ECCS architecture.